1988
DOI: 10.1002/chin.198831017
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Voltammetric Response of Zeolite‐Modified Electrodes

Abstract: ChemInform Abstract is investigated using the following analytes: methyl viologen dication (I), heptyl viologen (II), Ru(NH3)63+ (III), Fe(CN)63-(IV) and Cu2+. It is found that zeolites mixed with carbon paste give more reproducible and robust electrodes than films of zeolite/polystyrene on Pt or glassy carbon. Electrodes modified with zeolite Y concentrate (I), (III), and Cu2+ from dilute solutions, whereas (II) and (IV) are excluded from the zeolite (due to charge and size, resp.). The zeolite A, having smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 1 publication
3
26
0
8
Order By: Relevance
“…The alteration of peak potential indicated that the metal complex is encapsulated inside the zeolite matrix and not present on the external surface. If there is any drastic decrease in peak currents for zeolite modified electrode, then the electron transfer occurs via extra-zeolite mechanism [32][33][34]. It was observed that CV of the encapsulated complex showed no decrease in peak currents, found to be independent of scan rate and was stable over an extended period of time without any change in redox potential values (Fig.…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…The alteration of peak potential indicated that the metal complex is encapsulated inside the zeolite matrix and not present on the external surface. If there is any drastic decrease in peak currents for zeolite modified electrode, then the electron transfer occurs via extra-zeolite mechanism [32][33][34]. It was observed that CV of the encapsulated complex showed no decrease in peak currents, found to be independent of scan rate and was stable over an extended period of time without any change in redox potential values (Fig.…”
Section: Electrochemical Studiesmentioning
confidence: 99%
“…The electrochemical properties of the ZMEs were tested by reproducing the cyclic voltammetry (CV) experiment of Shaw et al [13] for a zeolite-Y polystyrene electrode, using Cu 2+ as the probe species. For the experiment ZMEs were obtained by the traditional method of dropwise coating a bare Pt electrode with polystyrene in methylene chloride-zeolite Y suspension, which was subsequently dried.…”
Section: Reagentsmentioning
confidence: 99%
“…The novel properties of ZMEs of analyte preconcentration, ion exchange and ion-selectivity based on size, shape, and charge selectivity of zeolites have made them not only extensively studied, but widely used in electroanalysis and electrocatalysis [2][3][4][5][6][7][8][9]. Several extensive reviews of preparation methods [10,11], the use of ZMEs with various electrochemical probes, the influence of supporting electrolyte, the molecular and electronic transfers, the solid state chemistry, and other numerous applications have been described [12][13][14]. There also has been much progress in understanding the importance of ion change and intrazeolite electron transfer and transport of ZMEs [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For analytical applications, it is highly desirable to develop robust modified electrodes that can be prepared easily and reproducibly. Additionally, by using a suitable modifier, it is desirable to improve sensitivity, detection limit and selectivity [40]. In the present work, we have attempted to improve the response characteristics of the Co-Z by incorporating the modifier in carbon-paste matrix.…”
Section: Introductionmentioning
confidence: 99%